Funcionamiento y conservación de un archivo audiovisual, experiencia en la videoteca de prensa de América Televisión - Bustamante Mondragón, Blanca Rosa (2022)
This professional sufficiency work summarizes twenty-five years of work experience in different media; fifteen of which I made in the Video Library/Press Archive of América Televisión and it focuses on the description, analysis and reflection based on my work as Video Library Assistant and how the technological changes that have occurred have affected the progress and conservation of the archive of video. This period has allowed me to acquire knowledge of the national and international news environment generated by the information produced daily and disseminated through the different newscasts of the channel. At the same time, closely observe the news production process and the importance of the file in the system, which supports journalistic work and editing work with images and information. This process ends with the archiving, classification and saving on the server of all this audiovisual material and the entry of all the information generated into a database. I finished my university studies in the year 1996-2 in the Faculty of Communication Sciences, followed by years of internships and work in different media, which solved my work experience and knowledge of the national journalistic, news and television media. Throughout these years I have worked as an editor, reporter and photographer specialized publications; also in writing and production of educational material and finally in image, archive, database and research on various topics.